2008
DOI: 10.1111/j.1445-2197.2008.04613.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Surgical Treatment of Younger Patients With Breast Cancer in Australia and New Zealand

Abstract: Between 1999 and 2006, the use of BCS for early breast cancer treatment in younger women was stable. These results show that surgeons contributing data to the National Breast Cancer Audit appear to use pathological factors that are known to increase the risk of local recurrence after BCS, in selecting mastectomy for younger women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…This study has used data submitted over the last 8 years by breast surgeons in Australia and New Zealand. One previous study has shown that over this period of time, the use of BCS has not changed significantly either overall (27), or for younger women using multivariate models (28). In the multivariate logistic regression analysis, we have checked and ensured that assumptions underlying the logistic modeling, such as a lack of co-linearity, were satisfied.…”
Section: Discussionmentioning
confidence: 99%
“…This study has used data submitted over the last 8 years by breast surgeons in Australia and New Zealand. One previous study has shown that over this period of time, the use of BCS has not changed significantly either overall (27), or for younger women using multivariate models (28). In the multivariate logistic regression analysis, we have checked and ensured that assumptions underlying the logistic modeling, such as a lack of co-linearity, were satisfied.…”
Section: Discussionmentioning
confidence: 99%
“…The data support clinical audit by surgeons of their practices and are used for research into breast cancer and its management. [1][2][3][4][5] The Audit's main purpose is to strengthen quality improvement through the promotion of high clinical standards, but it is recognised that cancer outcomes would also be affected by structural features of the health system, potentially including governance structures, resource allocation, service coordination, workforce availability, and access and appropriateness of care. [6][7][8] For example, poor survival from cancer among Aboriginal and Torres Strait Islander patients has been associated with geographic remoteness, cultural differences, socioeconomic and other social factors not adequately accommodated by the health system, rather than technical standards of care delivered.…”
Section: Introductionmentioning
confidence: 99%
“…An opportunity exists to explore age‐related survivals from early breast cancer using data from the National Breast Cancer Audit (NBCA) of the Royal Australasian College of Surgeons (RACS). These data have been collected since 1998 primarily to support clinical audit by surgeons of their practices 14–16 …”
Section: Introductionmentioning
confidence: 99%